Perbaikan pengelolaan sampah rumah tangga dan sampah kebun di Gampong Meunasah Papeun Kabupaten Aceh Besar [Improving household and garden waste management in Meunasah Papeun Village, Aceh Besar District] - Hasan, Hafidh; Haryani, Sri; Zainabun, Z; Wahyuni, Sri; Sofyan, Hamny (Universitas Syiah Kuala, 2024)
The waste problem in Aceh Besar District has been going on for quite some time now, which root cause can be tracked back to the lack of waste collection and treatment facilities compared to its residents waste growth. Therefore, the amount of untreated waste continues to increase. Meunasah Papeun Village as one of the villages in Aceh Besar District also faces the same problem, where the facilities and capacity of the Village Waste Management Unit (VWM) cannot keep up with the growth of residents' waste. Untreated waste ends up in illegal dumps or is burned by residents. This has reduced the comfort and quality of the village environment. In this Community Development Program (CDP), an approach was taken to reduce the waste that ended up in landfills through education and training on recycling and composting. The process sorted waste into three categories: organic, non-organic and residual waste. Some organic waste was composted and the rest became residue. Non-organic waste was sorted into recyclable and residual groups. This CDP was carried out in collaboration with Bank Sampah USK (BSU) to collect residents' recyclable waste. The residual was collected by VWM to be sent into the landfill. The residents who participated in these activities were able to cut their waste from a third to more than half. The extra money from recycling that was deposited into BSU was an additional advantage.